Accidental Entry of Fish into Throat While Bathing in a Pond. (25th November 2013) - Parida, Pradipta Kumar; Surianarayanan, Gopalakrishnan
Abstract : While fish bones are common foreign bodies in the throat, a whole live fish in the pharynx is very rare. We report a case where a whole fish accidentally entered the throat of a 52-year-old male, where it became lodged causing throat pain and dysphagia. The fish was removed as an emergency procedure.